Peningkatan Kemampuan Maharah Al-Qira’ah Bagi Siswa-Siswi Kelas VII-K Melalui Model Pembelajaran Inquiri Di Madrasah Tsanawiyah Negeri 2 Malang - Fatimah, Siti; Mukmin, Muhammad Islahul x; Saifudin, Achmad (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Learning Arabic is divided into four maharah, including Maharah al-qira’ah. Maharah al-qira’ah is a skill focused on the ability to read and understand texts. In learning al-qira’ah maharah, the writer found a problem in class VII-K MTsN 2 Malang, where many students have not been able to read texts without hesitation and difficulty understanding the contents of the text. Therefore, it requires a learning model, one of them is an inquiry model. The inquiry model is a learning model by conducting search and inquiry activities, so students are able to formulate their own findings. In this model, students play an active role during learning. They find the material being studied and solve the problem themselves. So, this model can solve learning problems that occur. Therefore, this research was carried out aimed at finding out the results of increasing al-qir'aah's ability with the inquiry model. This study uses a qualitative and quantitative (combined) approach to the classroom action research model. Research data sources are students through tests, observations, interviews and documentation. The researcher used a qualitative analysis of Miles and Huberman and Paired Sample T-test T-test. The results of this study are al-qira'ah maharah learning through inquiry learning model for students of class VII-K in MTsN 2 Malang increase student understanding and are very influential for the success of students in al-qira'ah maharah by evidencing an increase in the average value the average obtained by students is 22.79